Foot Care Knowledge and Education In An Effort To Prevent The Recurrent Of Diabetic Foot Ulcer (Dfu) - Eva Arna Abrar; Fitri A Sabil; Yusran Haskas; Suarnianti; Azniah Syam (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Diabetic Foot Ulcer (DFU) is a complication of Diabetes Mellitus (DM), which is a major health problem throughout the world with a high recurrence rate. It is estimated that approximately 40% of patients have a recurrence within one year of ulcer healing, nearly 60% within three years, and 65% within five years. One of the efforts to prevent DFU recurrence can be made with foot care which is preceded by knowledge of foot care. This study aimed to compare the knowledge of DFU patients before and after being given education. This study is a pre-post-test with 21 respondents who routinely received wound care at Rumah Perawatan ETN CENTER. Measurement of initial knowledge using a questionnaire consists of 11 questions that have been tested for content validity (CVI > 80%). Then the patient is given foot care education using a video, and after that, the video link is distributed to the patient; patient knowledge was measured again after three weeks using the same questionnaire. There is a comparison of knowledge before and after being given foot care education with a p-value = 0.000. Foot care is one of the efforts to prevent recurrent DFU. There was an increase in patient knowledge after being given an education